The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1038/s41598-020-60946-y
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of miRNAs and their targets during early somatic embryogenesis in Dimocarpus longan Lour.

Abstract: miRNAs are endogenous regulatory factors that play pivotal roles in post-transcriptional regulation. However, their specific roles in early somatic embryogenesis (SE) remain unclear. Study of the SE system is fundamental for clarifying the molecular mechanisms in Dimocarpus longan. We identified 289 known miRNAs from 106 different miRNA families and 1087 novel miRNAs during early longan SE, including embryogenic callus (EC), incomplete pro-embryogenic culture (ICpEC), globular embryo (GE), and non-embryogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 63 publications
(49 reference statements)
4
19
0
Order By: Relevance
“…Consequently, we hypothesised that the methylation of the AuxRE motifs in the promoters of the LEC1 , LEC2 , BBM and WUS genes might recruit the methylation-sensitive ARFs that have a regulatory function in SE induction [ 92 ]. In Arabidopsis, a high number (over 75%) of TFs was estimated as being methylation-sensitive, including the ARF5/MONOPTEROS [ 93 ], which has been reported as playing role in SE induction [ 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 ]. Whether the auxin-controlled differential methylation of the TF gene promoters affects the binding of auxin-responsive regulatory proteins, including ARF5, to the promoters of the SE-involved genes, requires experimental confirmation.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, we hypothesised that the methylation of the AuxRE motifs in the promoters of the LEC1 , LEC2 , BBM and WUS genes might recruit the methylation-sensitive ARFs that have a regulatory function in SE induction [ 92 ]. In Arabidopsis, a high number (over 75%) of TFs was estimated as being methylation-sensitive, including the ARF5/MONOPTEROS [ 93 ], which has been reported as playing role in SE induction [ 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 ]. Whether the auxin-controlled differential methylation of the TF gene promoters affects the binding of auxin-responsive regulatory proteins, including ARF5, to the promoters of the SE-involved genes, requires experimental confirmation.…”
Section: Discussionmentioning
confidence: 99%
“…Also, miR397b-3p was up-regulated in the callus of both E. camaldulensis and E. grandis x urophylla, and miR397a-3p was up-regulated only in the dedifferentiated tissue of E. camaldulensis (Additional le 3). Like MIR397, MIR159 has been studied to regulate the development of callus in multiple plants, such as Dimocarpus longan [21,22], Moringa oleifera [23] and Larix leptolepis [24]. miR159 has been shown to be induced by ABA and to regulate MYB33 during the seed germination of Arabidopsis [25].…”
Section: Discussionmentioning
confidence: 99%
“…We identified a total of 183 miRNAs (92 conserved and 91 novel miRNAs) by next-generation sequencing. Previous studies on miRNAs, including Xu et al[30] identified 289 known miRNAs and 1087 novel miRNAs in longan, while Wu et al [26] reported 50 known and 45 novel miRNAs in citrus. Taken together, these data show that distinct types of miRNAs are expressed at different levels during the process of regeneration in different species.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the large scale application of next-generation sequencing has proved to be a useful tool to identify the patterns of miRNA expression during plant regeneration. Genome-wide miRNAs and their targets have been analyzed during explant regeneration in vitro in wheat[21], rice[22, 23], cotton[24], peanut[25], sweet orange [26], coconut[27], larch[28], maritime pine[8], Norway Spruce[29], longan[30], yellow-poplar[31], radish[32], Lilium [33], and Tuxpeno maize[34]. However, all these studies were performed on in vitro specimens, which relys on the presence of exogenous hormones to regenerate plantlets.…”
Section: Introductionmentioning
confidence: 99%